"A Dança Circular Sagrada e o Sagrado": um estudo exploratorio das relações históricas e práticas de um movimento "New Age", em busca de seus aspectos numinosos e hierofânicos - Berni, Luiz Eduardo Valiengo (2002)
The Sacred Circle Dance is a contemporary practice of dance which aims to rescue its primordial function when it was incorporated to an integrate complex called Music-Dance-Prayer; its original function is self-knowledge and transcendence. German born Benhard Wosien started the Movement in the 70´s and The Spiritual Community of Findhorn in the northeast of Scotland spread these practices throughout the world. The Movement was born during the emerging of the New Age culture. This work is an exploratory study of the historic-practical dimension of this Movement; it is an attempt to identifiy its traditional origin as well as trying to find its relation with the phenomenological aspects of the Sacred in Rudolf Otto, Mircea Eliade and Ninian Smart. Therefore, the origins of the Circle Dance as well as the contemporary correlative movements throughout history have been investigated. Besides the bibliographic study, a qualitative investigation with ten Brazilian facilitators from different regions of that country was carried out aiming to describe not only their profile but mainly their relation with the numinous. The conclusion is that there is a tendency to reintegrate with the original complex Music-Dance-Prayer and only the Fascinans, the most common aspect of the numinous has been present. This work suggested new questions for future investigations